Forest GPP Calculation Using Sap Flow and Water Use Efficiency Measurements - Fyodor Tatarinov; Eyal Rotenberg; Dan Yakir; Tamir Klein (Bio-Protocol, 2017)
This is a protocol to evaluate gross primary productivity (GPP) of a forest stand based on the measurements of tree’s sap flow (SF), 13C derived water use efficiency (WUE), and meteorological (met) data. GPP was calculated from WUE and stomatal conductance (gs), the later obtained from SF up-scaled from sampled trees to stand level on a daily time-scale and met data. WUE is obtained from 13C measurements in dated tree-ring wood and/or foliage samples. This protocol is based on the recently published study of Klein et al., 2016.